(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Introduction: The purpose of this study is to formulate cephalometric norms of the Bangladeshi population using Downs Analysis; and to evaluate whether significant cephalometric differences exist between Bangladeshi and Caucasian people. Methods: The study was conducted for 91 Bangladeshi young adults (48 males and 43 females), aged 19–27 years, with esthetically pleasing and harmonious faces, Angle I molar relationship, with all permanent teeth present and no history of orthodontic treatment orofacial trauma. Lateral cephalograms taken of these subjects were used for a series of morphometric analysis. Results: There was a significant difference between the genders on some values. Bangladeshi Female showed significantly larger facial angle more protrusive chin and angle of convexity which is more protrusive maxillary part than that of Males. While Bangladeshi male showed significantly greater Y-axis angle that means downward forward growth pattern, and steeper Cant of occlusal plane than that of females. Statistically, several significant differences were noticeable in the results of the present study when compared with the norms suggested for a white Caucasian population by Downs. Bangladeshi’s exhibit significantly smaller facial angle more retrusive mandible, significantly greater Y-axis angle more downward forward growth pattern and also significantly more protrusive anterior teeth than that of the Caucasian population. Conclusion: These results have clinical implications in the diagnosis and treatment of adult Bangladeshis with dentofacial deformities. J Bangladesh Coll Phys Surg 2024; 42: 149-154